2011
DOI: 10.1002/pits.20580
|View full text |Cite
|
Sign up to set email alerts
|

Fostering social–emotional resilience among Latino youth

Abstract: National statistics reveal that Latino youth face significant challenges and engage in many risky behaviors that can hinder positive development and well-being, such as attempted suicide, lifetime cocaine use, unprotected sex, and dropping out of school. However, these statistics obscure the fact that many Latino youth are developing well despite exposure to significant adversity. A critical question that lies before researchers, educators, and policy makers is how to improve the health, well-being, and achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 41 publications
4
50
0
1
Order By: Relevance
“…Although participants did not want to be singled out for their differences, they placed high value on the opportunity to see and interact with others like them who had succeeded. In line with previous research that espoused the importance of social connections (Grant-Vallone et al, 2004;Herrera et al, 2011;Hirt et al, 2008;Morales, 2010;Palmer & Young, 2009;Reyes, 2011;Torres & Hernandez, 2009), our participants all reported that personal attention received from professors and friends provided important motivation and helped nurture inward perseverance.…”
Section: Research Question 4: What Recommendations Do the Participantsupporting
confidence: 79%
“…Although participants did not want to be singled out for their differences, they placed high value on the opportunity to see and interact with others like them who had succeeded. In line with previous research that espoused the importance of social connections (Grant-Vallone et al, 2004;Herrera et al, 2011;Hirt et al, 2008;Morales, 2010;Palmer & Young, 2009;Reyes, 2011;Torres & Hernandez, 2009), our participants all reported that personal attention received from professors and friends provided important motivation and helped nurture inward perseverance.…”
Section: Research Question 4: What Recommendations Do the Participantsupporting
confidence: 79%
“…In addition, few studies are conducted in classrooms with a high concentration of Latino students. Given the relationally oriented values in many Latino communities (Reyes & Elias, 2011;Rivera & RogersAtkinson, 1997), Latino students' relationships with teachers and peers may be particularly important to students' behavioral engagement.…”
Section: Supportive Social Processes: Role Of Individual Relationshipmentioning
confidence: 99%
“…In classrooms where the teacher may not be providing support, these connections may provide access to emotional and academic resources that facilitate academic development (Dika & Singh, 2002). Peer connections may be particularly important for students from Latino families and communities where relationally oriented values such as helping others and building positive relationships are culturally emphasized (Clauss-Ehlers & Lopez Levi, 2002;Reyes & Elias, 2011). Emerging research examining interaction patterns in social relationships (e.g., non-linear dynamics: Dishion, Forgatch, Van Ryzin & Winter, 2012) may further our understanding of social connections and the transmission of social capital among students.…”
Section: Individual Relationships With Teachers and Peers: Predictingmentioning
confidence: 99%
See 1 more Smart Citation
“…Both African American (Hines & Boyd-Franklin, 1982; Tyler, Boykin, Miller, & Hurley, 2006) and Latino (Cardoso & Thompson, 2010; Reyes & Elias, 2011) cultures historically have emphasized the importance of interpersonal relationships with individuals outside of the nuclear family, including extended family members and fictive kin. Consistent with this idea, studies of relationships with NPAs have found that ethnic minority adolescents report higher numbers of NPAs, as well as closer relationships with NPAs, compared to White adolescents (Hirsch, Mickus, & Boerger, 2002; Pallock & Lamborn, 2006 ).…”
Section: Introductionmentioning
confidence: 99%